2018
DOI: 10.1016/j.virol.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded viral RNA persists in vitro and in vivo during prolonged infection of porcine reproductive and respiratory syndrome virus

Abstract: In order to study the mechanism of PRRSV persistence, an in vitro model of persistence was developed by serially passaging PRRSV-infected MARC-145 cells 109 times. Viral persistence was detected to be associated with increased double-stranded (dsRNA) in the infected cells. In PRRSV infected pigs, reduced ratio of plus to minus strands of viral RNA was observed in lymphoid tissues from PRRSV persistent pigs at 52 days post infection. Viral dsRNA was mostly detected in the germinal center during persistent infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This finding attests for the unprecedented ability of the novel isolate to manipulate cell machinery to circumvent cell death and demands for further studies to understand the molecular mechanisms underlying its persistent infection. Nidovirales and, among them, coronaviruses are prone to establish persistence both in vivo and in vitro [ 36 ]. It is well admitted that persistence results from adaptations of both the host cell and the virus [ 37 ] and that mutations in the viral genome concur to the persistence [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding attests for the unprecedented ability of the novel isolate to manipulate cell machinery to circumvent cell death and demands for further studies to understand the molecular mechanisms underlying its persistent infection. Nidovirales and, among them, coronaviruses are prone to establish persistence both in vivo and in vitro [ 36 ]. It is well admitted that persistence results from adaptations of both the host cell and the virus [ 37 ] and that mutations in the viral genome concur to the persistence [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported previously that no significant DEGs were observed in lymphoid tissue of persistently infected animals [ 26 ]. In the current study, we identified a large number of DEGs in persistently infected animals ( Figure 2 b).…”
Section: Discussionmentioning
confidence: 98%
“…Viral RNA reads were detected in ILN of all five infected pigs. It was reported previously that PRRSV genome mainly exists in dsRNA forms in lymphoid tissues during persistent infection [26]. Since only mRNA (purified by using poly-T oligo-attached magnetic beads) was used for library construction and RNA sequencing, the viral RNA reads detected in this study must be derived from either viral genomic RNA or sub-genomic mRNA, not from dsRNA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations